Metaphysics as a science in the "Summa Contra Gentiles" of St. Thomas Aquinas. - Pasichny, Cornelius John. (University of Ottawa (Canada), 1956)
The general historical study of the works of St. Thomas under the aspect of metaphysics has for its purpose the reconstruction of Thomistic metaphysics. This thesis is a contribution to that study. In its present form it is concerned with metaphysics as a science as exposed in the Summa Contra Gentiles . The first chapter considers the texts which deal with the objects of metaphysics and show that God holds a special place in a metaphysical inquiry. Created things are studied both in themselves and with regard to their principle and end, and especially under the aspect of their perfection of being. For it is proper to metaphysics to study common or universal being, which in most cases is considered to be the perfection of finite things. Common being can, however, also be considered a perfection applicable to God and creatures. Thus, among the objects of metaphysics there are finite and infinite things. To establish an order among these objects, we turn to a study of texts which deal with our mode of acquiring knowledge, and we find that we must necessarily begin with finite sensory things. For on the knowledge of these is based our knowledge of being and the first principles of being. Therefore, finite things are first in our order of knowledge. God, however, is the most noble object of metaphysics, even if He is the last known by us. It follows, then, that at the outset of metaphysics we know the perfection of being of finite things alone, and only at the term, after proving the existence of God, are we able to see the concept of being in its full transcendality as applying to God and creatures. God is not the first known and that through which all else is known, but He is the most noble object known in metaphysics. Since the perfection of being is possessed by God and creatures, we study, in the second chapter, the analogy of being. When Aquinas employs the term of analogy, he has in mind the analogy of causal relation or attribution. But when he deals with perfections said of God and creatures, he speaks of intrinsic possession on both sides, and therefore has the elements of the analogy of proper proportionality. In the third chapter we treat of the origin of metaphysics in man. He is dependent for it upon God as he is in being and action. The function proper to metaphysics or wisdom is to order, and to do effectively, one must possess the knowledge of the last end of things. The reward of wisdom in a natural happiness. Finally, in the fourth chapter, we discuss four recent articles on metaphysics in order to bring out the differences that are to be found in the various approaches to metaphysics and to stress the need for a systematic study of the writings of Aquinas himself.
Keywords: Religion, Philosophy of.